A system for detecting fluorescent tracers in streamflow - Steppuhn, Harold Wolfgang, author; Meiman, James R. (James Richard), advisor; Dils, Robert E., committee member; Harris, David V., committee member; Johnson, Gestur, 1910-, committee member; Duke, Harold R. (Harold Ray), 1940-, committee member (Colorado State University. Libraries, 1970)
A system is developed capable of continuously monitoring the relative concentration of a fluorescent tracer in streamflow. Streamside instrumentation automatically registers stream-borne tracer concentrations as a function of time on a gelatin-coated film. The film is routed through a device which passes a continuous sample-aliquot diverted from the tracer-dosed stream over a small segment of the film. The "exposed" film is periodically gathered from stream sites and analyzed in a laboratory-based fluorometer. Utility of the system is studied for the gaging of streamflow to produce a hydrograph, to measure stream discharge instantaneously, and to determine time-of-stream-travel. Hydrographs resulting from 640 hours of gaging two Colorado mountain streams with the system are compared to those obtained from closely located sharp-crested weirs. The maximum instantaneous deviation between hydrographs reaches 10% and average absolute departure equals 1.8%, while algebraic departure averages +0.3%. The practicality of using this system to obtain time-of-stream travels is demonstrated for five Colorado mountain streams. A total of 62 traveling tracer-clouds are registered on gelatin-coated film, from which time-of-stream-travels are determined. Processes involved in the system and factors affecting its precision are investigated. Theoretical and experimental evidence strongly indicates that the bulk of tracer uptake by gelatin follows processes that are physical rather than chemical in nature. Stream temperature changes and duration of film-tracer contact are the two most important factors affecting precision of the system. Neither major factor caused any unsolvable problem when field operations were standardized. The system will have utility in operations where an expensive, temperature-sensitive fluorometer can not be stationed stream-side, and where the particular objectives of stream measurements do not justify the cost of conventional techniques, but where fair accuracy and continuous records of short to moderate duration are desired.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Stream measurements -- Colorado; Fluorimetry